Spatial organization of tourist attraction network of Kryvorizhzhia - Shiyan, Daria; Kazakova, Tetiana; Sonko, Sergii (Human Geography Journal, 2018)
Technogenic tourism, as a relatively young trend in tourism, begins to play a significant role in Kryvbas, one of the oldest industrial regions in Ukraine. It has preserved the industrial heritage of the previous industrial and technological structure. Considering the considerable length and the total area of Kryvbas, classical methods of spatial research, in particular, the model of spatial optimization of access areas of Thiessen-Voronoi, can be effectively applied to studying, in particular, its tourist resources. In our case, 48 points that correspond to certain tourist attractions form a network with different levels of transport access. The basis was the digital map of Kryvbas, made in MapInfoProf environment in previous author’s works. Next, with the special option of MapInfoProf, Voronoi polygons were developed which became the tool for further spatial analysis. Actually, the results of such analysis allowed to clarify the recreational and technogenic zoning of Kryvbas, as well as to study main laws of spatial organization of tourist attraction network of the region. Peculiarities of the modern spatial organization of tourist attraction network of Kryvorizhzhia encourage the conclusion on the presence of two major regions of the development of technogenic tourism within Kryvyi Rig. The first region is more developed Central-Southern with higher density and smaller average area of Voronoi polygons. The second one is the Northern with smaller number and larger average area of Voronoi polygons, as well as one that is more promising for the development of technogenic tourism. The results of the study will be useful in planning routes for tourist logistics.